BIMP-EAGA VISION 2025 AND SUBREGIONAL COOPERATION FOR FOOD SECURITY IN MINDANAO - Rara Gusnita Putri; Regiana Revilia (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Mindanao, a key agricultural region in the southern Philippines, is increasingly vulnerable to climate-induced food crises. Recent hydro meteorological disasters, notably floods, have caused crop failures across more than 20,000 hectares of rice fields and 8,800 hectares of staple crops, threatening local food supply stability. These challenges are compounded by limited human resource capacity in agricultural sectors and fragmented domestic policy responses. Within this context, the BIMP-EAGA Vision 2025 offers a strategic platform for sub regional cooperation, aiming to strengthen food security through climate adaptation strategies, agricultural technology transfer, and regional trade facilitation. This study employs a qualitative approach and policy analysis to examine the mechanisms through which BIMP-EAGA contributes to mitigating the food crisis in Mindanao. Three focus areas are analyzed the establishment of a food security corridor to stabilize commodity supply chains, capacity building for farmers through cross-border knowledge and technology exchange, and mobilization of agricultural infrastructure funding within the Vision 2025 framework. The findings reveal that BIMP-EAGA’s cooperative initiatives have enhanced access to regional food reserves and facilitated cross-border trade, reducing the immediate impacts of crop failures. However, implementation remains constrained by disparities in resource allocation, institutional coordination gaps, and policy misalignments between member states. This study addresses a significant research gap by providing an in-depth analysis of how Vision 2025 operationalizes food security measures at a sub-regional scale, offering insights into policy harmonization for climate-resilient agriculture in Southeast Asia.